2023
DOI: 10.3390/cancers15030723
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Sarcopenia’s Occurrence during Radiotherapy in Oropharyngeal Cancer Patients

Abstract: The current study aims to profile sarcopenic condition (both at baseline and developed during treatment) in oropharyngeal carcinoma (OPC) patients treated with curative radiotherapy (RT) +/− chemotherapy and to evaluate its impact on oncological outcomes and toxicity. A total of 116 patients were included in this retrospective single-center study. Sarcopenia assessment at baseline and at 50 Gy re-evaluation CT was obtained from two different methodologies: (i) the L3-skeletal muscle index (SMI) derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Also, Karavolia et al 36 demonstrated, in a large cohort of 977 head and neck patients, that sarcopenia was an independent prognostic factor for the development of physician-rated acute grade ⩾ 3 dysphagia and late grade ⩾ 2 and grade ⩾ 3 dysphagia, probably for its impact on the swallowing glands. On the contrary, Huang et al 37 and, very recently, Bergamaschi et al 38 could not find an association between sarcopenia and radiotherapy toxicity in 82 nasopharyngeal cancer patients and 116 oropharingeal cancer patients respectively. In our series the acute toxicity profile was not significantly higher in low SMI patients, even if a tendency to a reduced tolerance to radiotherapy could be found.…”
Section: Discussionmentioning
confidence: 91%
“…Also, Karavolia et al 36 demonstrated, in a large cohort of 977 head and neck patients, that sarcopenia was an independent prognostic factor for the development of physician-rated acute grade ⩾ 3 dysphagia and late grade ⩾ 2 and grade ⩾ 3 dysphagia, probably for its impact on the swallowing glands. On the contrary, Huang et al 37 and, very recently, Bergamaschi et al 38 could not find an association between sarcopenia and radiotherapy toxicity in 82 nasopharyngeal cancer patients and 116 oropharingeal cancer patients respectively. In our series the acute toxicity profile was not significantly higher in low SMI patients, even if a tendency to a reduced tolerance to radiotherapy could be found.…”
Section: Discussionmentioning
confidence: 91%